2018
DOI: 10.1001/jama.2018.12291
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Naloxone Without a Prescription by California Pharmacists 2 Years After Legislation Implementation

Abstract: Layperson access to the opioid overdose reversal medication naloxone can reduce mortality. 1,2 Legislation in California has allowed trained pharmacists to furnish naloxone without a physician's prescription since January 27, 2016. 3 Under a Board of Pharmacy protocol, naloxone is available by patient request or pharmacist suggestion. A furnishing pharmacist is required to screen and educate patients on opioid overdose prevention, recognition, and response.With patient consent, the pharmacist must notify the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 5 publications
2
92
0
Order By: Relevance
“…35 This role for pharmacists has been recognized at the state and national levels by making policies more conducive to enabling pharmacists to address the opioid overdose crisis. 29,59,60 All 50 states had implemented enhanced pharmacy naloxone access laws by 2018, and 19 states required naloxone education for pharmacists engaged in naloxone dispensing or prescribing. 47 The standing orders issued by most states allow pharmacists to dispense naloxone via protocol without a written order from a physician, which makes it possible for pharmacists to screen patients at risk of overdose, dispense naloxone, and educate individuals about using naloxone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 This role for pharmacists has been recognized at the state and national levels by making policies more conducive to enabling pharmacists to address the opioid overdose crisis. 29,59,60 All 50 states had implemented enhanced pharmacy naloxone access laws by 2018, and 19 states required naloxone education for pharmacists engaged in naloxone dispensing or prescribing. 47 The standing orders issued by most states allow pharmacists to dispense naloxone via protocol without a written order from a physician, which makes it possible for pharmacists to screen patients at risk of overdose, dispense naloxone, and educate individuals about using naloxone.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the standing orders, a widespread issue of pharmacists not stocking naloxone is reported. 36,[59][60][61] Given the need and potential for this role, an important question is how to facilitate a more complete actualization of the role.…”
Section: Discussionmentioning
confidence: 99%
“…Robust PDMPs were less consistently associated with reduced percentage of patients prescribed opioids, with the magnitude and significance of the effects varying by state. The authors also assessed the effect of robust PDMPs on opioid prescriptions filled by three or more prescribers and pharmacists, observing a decrease only in Kentucky, compared to Mississippi, but not in the other state pairs …”
Section: Resultsmentioning
confidence: 99%
“…11 Multiple studies have found that student pharmacists report greater confidence in dispensing and counseling on naloxone after live hands-on training. [12][13][14][15] Increased comfort with expanded access to naloxone may also result from continuing to address stigma against opioid use disorder, which persists among the public and even among health professionals. 16,17 2019.3dRole of pharmacists and pharmacy education in patient care involving cannabis Use of cannabis and related products has risen in recent years.…”
Section: 1daddressing Professional Burnoutmentioning
confidence: 99%